Quel droit social en Europe face au capitalisme de plateforme ? - Josépha Dirringer (La Nouvelle Revue du Travail)
The rise of platform capitalism has gone hand-in-hand with a transformation of forms of employment and work in France and elsewhere. The need to create new forms of regulation – and the opportunity that this represents - has never been more palpable than in recent years. Actual and proposed reforms have proliferated as efforts are made to formulate a body of social law that protects all workers, irrespective of their legal subordination or economic dependence. The article presents possible ways in which this might happen. Beyond the technical redefinition of worker status, it investigates which pathway is most apt to maximise workers’ protection and empowerment. The premise here is that rethinking the boundaries of wage-earning does not suffice. Rather, it is crucial that consideration be given to the best way of reformulating social rights and creating new forms of social solidarity.